Penggunaan Campuran Abu Sampah Organik dan Limbah Karbit sebagai Bahan Pengganti Semen pada Mortar - Edi Hartono; Siti Rofi’ah ZA; Abd Dzargifar Hemeto (Universitas Muhammadiyah Yogyakarta, 2009)
Organic waste and calcium carbide waste can be used as replacement material for cement in mortar. Organic waste ash and calcium carbide waste are mixed with some variations and then conducted tests to obtain the characteristics of the materials used in this study. Content of mortar comparation base on weight that are organic waste-calcium carbide waste : sand : water of 1.0 : 2.75 : 1.0. Compositions of waste organic ash and calcium carbide waste have some variations, i.e., 0.9-0.1, 0.7-0.3, 0.5-0.5, 0.3-0.7 and 0.1-0.9. Control mortar also made as discussant for mixture variations of organic waste ash and calcium carbide waste in compressive strength test. Control is mortar mixed with common Portland cement. All of mortars are mold with molder that has dimension 5 cm × 5 cm × 5 cm. Compressive strength test is done when age of mortars is 3 days, 14 days, and 28 days. Based on laboratory test results, compressive strength on 14 days at the highest variation of 70 % organic waste ash and 30 % calcium carbide waste was found to be 26,7 kg/cm2. But, this result of compressive strength is lower compared to compressive strength of control mortar which was found to be 79.9 kg/cm2 on 14 days. Highest compressive strength of all mixture variation showed that mixture of waste organic ash and calcium carbide waste can be used as a mortar/mixture of brick pair in simple house type and very simple house type that needs compressive strength as much as 25 kg/cm2for wall that do not bear of load.